Two new species of the genus Neoseiulus Hughes (Acari: Phytoseiidae) from Greece with re-description of Neoseiulus leucophaeus (Athias-Henriot) - Stathakisis, Theodoros I.; Kapaxidi, Eleftheria V.; Papadoulis, Georgios Th. (Zootaxa, 2013)
Two new species, Neoseiulus elisiensis n. sp. and Neoseiulus neomarginatus n. sp., are described from Greece. Neoseiulus leucophaeus (Athias-Henriot) is re-described and illustrated based on specimens collected on Thymelaea hirsuta (L.) Endl. A key to all species of the genus Neoseiulus Hughes reported from Greece is provided.